The Strategy Inquiry Based Learning in Growing Students' Religious Awareness - Radinata, Riki; Hernisawati, Hernisawati; Wijaya, Adi (International Journal on Advanced Science, Education, and Religion, 2025)
This research focuses on the use of IBL to increase the religious awareness of class VIII students at SMPN 1 Punggur, Central Lampung, where problems were found such as low participation in religious activities and poor social relations between students. The formulation of this research problem is how to strategy inquiry based learning and its impact on students' religious awareness? This research aims to explore the application of IBL strategies and their impact in fostering religious awareness. This research method uses descriptive qualitative, using methods such as participant observation, in-depth interviews, and document analysis. Informants in this research included: the principal, PAI teacher and class VIII students at SMPN 1 Punggur. The data validity test uses triangulation techniques. Then, after all the data has been collected, analysis will be carried out in three stages, namely data reduction, data display and conclusion drawing. The results showed that IBL significantly increased students' engagement with religious teachings and encouraged reflection on moral and spiritual values, leading to better understanding and implementation of religious rituals. Despite challenges in implementation by teachers and the need for further training, this research highlights the positive impact of IBL in fostering religious awareness and increasing students' social interactions. This approach offers a promising solution for improving religious education in schools, as well as contributing to the development of responsible and spiritually aware individuals.